Sosialisasi Moderasi Beragama: Merawat Kemajemukan Melalui Moderasi Beragama di Sekolah - Samel Sopakua; Sephliano E. M Sahureka; Johanes Waldes Hasugian; Risky Lekantompessy; Jus Benheis Teterissa (Abdimas Universal, 2023)
This article describes insights into religious moderation and strategies for treating pluralism in education. The purpose of this activity is to socialize the insight of religious moderation in a plural common life, provide awareness to always be wise and wise in responding to various issues that have the potential to divide the nation's children and offer principles and strategies in caring for pluralism for every education stakeholder. The method used is the presentation or presentation of material, questions, and answers, or discussions with the participants. The activity enriched participants' insights regarding religious moderation, besides educational institutions also have a strategic function or role in caring for the nation's plurality. Some principles or strategies that need to be considered in caring for pluralism include creating classes or schools that are anti-discrimination (free from discriminatory treatment), designing learning curricula that contain profiles of graduates who love pluralism, learning models that form moderate attitudes of students, building a culture of dialogue, implementing a reward system for students who behave tolerantly and respect others who have different identities. The community service carried out showed high enthusiasm or responsiveness from the participants and there was an interest in the issue of religious moderation.